Tensile properties of wire and fibre reinforced cementitious matrix composites for strengthening of masonry. (February 2020) - Padalu, Pravin Kumar Venkat Rao; Singh, Yogendra; Das, Sreekanta
Graphical abstract: Highlights: Mechanical characterization of welded wire mesh and WRCM composites. Mechanical characterization of basalt fibre mesh and BFRCM composites. Comparison of failure modes and properties of reinforcement with those of composites. Comparison of the test results with ACK and simplified tri-linear (STL) models. Abstract: Currently, wire and fibre reinforced inorganic matrices are receiving a lot of attention amongst the structural engineers, especially for strengthening of existing masonry structures. The motivation behind this development stems from the drawbacks of organic (epoxy resin) matrices of fibre reinforced polymers (FRP). A number of cement-based composites have been developed in the recent years in form of fibre reinforced cementitious matrix (FRCM) and wire reinforced cementitious matrix (WRCM) composites. Since the development of composites made of cementitious matrix is still under development, the evaluation of mechanical properties of such systems is a crucial step in their application. The tensile strength of the composite is an important parameter for the design of the strengthening system. This article presents an experimental study on 75 welded wire mesh (WWM) and basalt fibre mesh (BFM) reinforcement and corresponding composite specimens. The specimens are tested following the relevant ASTM and ACI standards. The mechanical behaviour of the composite is compared with the constituent reinforcement. The failure modes and tensile behaviour of the composites before and after cracking are also discussed. The test results are analyzed and compared with 'Aveston-Cooper-Kelly (ACK)' theory and the 'simplified tri-linear (STL) model'.